2017
DOI: 10.1080/07420528.2017.1315125
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal light imprinting of circadian clocks and systems (PLICCS): A signature of photoperiod around birth on circadian system stability and association with cancer

Abstract: Recent findings from animal models suggest that plasticity of human circadian clocks and systems may be differentially affected by different paradigms of perinatal photoperiod exposure to the detriment of health in later life, including cancer development. Focusing on the example of cancer, we carry out a series of systematic literature reviews concerning perinatal light imprinting of circadian clocks and systems (PLICCS) in animal models, and concerning the risk of cancer development with the primary determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 114 publications
(204 reference statements)
0
21
0
Order By: Relevance
“…Indeed, individuallevel data on potential effect modifiers not available in the present dataset, such as latitude, exposure to sunlight, type of outdoor activities, climatic changes and variations in seasonal infections, would be targets of future research to allow assessment of their potential role in CNS tumors risk, as shown in other childhood cancers. [55][56][57][58] Our results are derived from a large population-based collection of incident cases, which allowed sound analyses. In particular, two distinct analytic approaches were used, namely seasonal analyses by birth month using two statistical tests (Cuzick-Edward's and Walter-Elwood), as well as Poisson regression and meta-analyses by season of birth.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Indeed, individuallevel data on potential effect modifiers not available in the present dataset, such as latitude, exposure to sunlight, type of outdoor activities, climatic changes and variations in seasonal infections, would be targets of future research to allow assessment of their potential role in CNS tumors risk, as shown in other childhood cancers. [55][56][57][58] Our results are derived from a large population-based collection of incident cases, which allowed sound analyses. In particular, two distinct analytic approaches were used, namely seasonal analyses by birth month using two statistical tests (Cuzick-Edward's and Walter-Elwood), as well as Poisson regression and meta-analyses by season of birth.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Moreover, within any given zeitgeber multiplicity, entrainment is determined by both external intensity and internal susceptibility 2. Determinants of the strength of zeitgebers include intensity, duration, phase timing and periodic frequency while the susceptibility of the receiving organism to such information can be assessed by the phase of internal time (indicating a phase response curve),23 and potentially by circadian system robustness 24. In effect, multiple zeitgebers such as light, noise, meals or social contacts may act synergistically or antagonistically, that is, they interact in terms of their ‘push’ or ‘pull’ on circadian rhythm phase 2.…”
Section: Methodsmentioning
confidence: 99%
“…Photoperiod is the predominant time cue for circadian clocks that regulate myriad physiological processes, including blood pressure and fate of nutrients—processes that can affect cardiovascular disease. Importantly, perinatal photoperiods might imprint developing circadian systems and affect later life physiology 2…”
mentioning
confidence: 99%
“…Such studies would complement similar investigations under way using UK Biobank data 4. If differential risks associated with photoperiod were observed, further research could target the hypothesised circadian imprinting mechanism 2…”
mentioning
confidence: 99%